Sex differences in the response to resistance exercise training in older people. Issue 12 (28th June 2016) - Da Boit, Mariasole; Sibson, Rachael; Meakin, Judith R.; Aspden, Richard M.; Thies, Frank; Mangoni, Arduino A.; Gray, Stuart Robert
Abstract: Resistance exercise training is known to be effective in increasing muscle mass in older people. Acute measurement of protein metabolism data has indicated that the magnitude of response may differ between sexes. We compared adaptive responses in muscle mass and function to 18 weeks resistance exercise training in a cohort of older (>65 years) men and women. Resistance exercise training improved knee extensor maximal torque, 4 m walk time, time to complete five chair rises, muscle anatomical cross‐sectional area (ACSA) and muscle quality with no effect on muscle fat/water ratio or plasma glucose, insulin, triacylglycerol, IL‐6, and TNF‐ α . Differences between sexes were observed for knee extensor maximal torque and muscle quality with greater increases observed in men versus women ( P  < 0.05). Maximal torque increased by 15.8 ± 10.6% in women and 41.7 ± 25.5% in men, whereas muscle quality increased by 8.8 ± 17.5% in women and by 33.7 ± 25.6% in men. In conclusion, this study has demonstrated a difference in the magnitude of adaptation, of some of the outcome measures employed, in response to 18 weeks of resistance exercise training between men and women. The mechanisms underlying this observation remain to be established. Abstract : Healthy ageing is characterised by a loss of muscle mass and function with the consequences of this differing between men and women. Resistance exercise is known to be beneficial in the maintenance of muscle mass across the lifecourse. The current study has shown that the increases in muscle function with resistance exercise are lower in women compared to men.